Infrastructural Heterogeneity: Energy Transition, Power Relations and Solidarity in Kingston, Jamaica. Issue 2 (15th March 2023) - Pilo', Francesca
ABSTRACT: In cities of the Global South, socio-technical heterogeneity in electricity provision is a reality that has partially shifted debates to the diversity of arrangements beyond the grid. Building on the case of Kingston in Jamaica, this article focuses on the relationship between the grid and such heterogeneous configurations and considers how heterogeneity transforms existing power relations. By analyzing the different strategies that actors (the government, the electricity provider, different types of consumers) have developed to address different challenges (energy transition, non-technical losses, affordability, etc.), the article shows how this heterogeneity entails a political process that reshapes possibilities and constraints for governing, and being governed by, the electricity grid. This analysis suggests taking solidarity as a central dimension when considering how to govern heterogeneous configurations, including the relationships between consumers, types of socio-technical systems and neighborhoods.